AKOMODASI ‘URF TERHADAP UPAYA PRIBUMISASI FIKIH MU’ÂMALÂT DI INDONESIA - Akmal Bashori (DIKTUM: Jurnal Syariah dan Hukum, 2019)
Urf (tradition) is an aspect that can not be separated from humans, because â€˜urf is an integral whole with actions that are repeatedly practiced and agreed upon by the local community. This tradition becomes a cultural symbol in which the culture (â€˜urf) in the perspective of fiqh epicemology becomes one of the elements in its formulation. The effort of indigenous jurisprudence muâ€™Ã¢malÃ¢t through cultural channels reap a positive response in society that is still recognized its existence. Like the principle of mutual â€œlegowoâ€ (QS 4: 29), the tradition of "maro" in the fiqh of muâ€™Ã¢malÃ¢t is called mudharobah, tradis â€œIjonâ€ (salam). All of it gets the legitimacy of Jurisprudence because fiqh is responsive and accommodative to the â€˜urf, in addition to the basic law of fiqh muâ€™Ã¢malÃ¢t is permissible.